Convergent multi-miRNA Targeting of ApoE Drives LRP1/LRP8-Dependent Melanoma Metastasis and Angiogenesis - Pencheva, Nora (2012)
Through in-vivo selection of human cancer cell populations, we uncover a convergent and cooperative miRNA network that drives melanoma metastasis. We identify miR-1908, miR-199a-5p, and miR-199a-3p as endogenous promoters of metastatic invasion, angiogenesis, and colonization in melanoma. These miRNAs convergently target Apolipoprotein E (ApoE) and the heat-shock factor DNAJA4. Cancer-secreted ApoE suppresses invasion and metastatic endothelial recruitment (MER) by engaging melanoma-cell LRP1 and endothelial-cell LRP8 receptors, respectively–while DNAJA4 promotes ApoE expression. Expression levels of these miRNAs and ApoE correlate with human metastatic progression outcomes. Treatment of cells with locked nucleic acids (LNAs) targeting these miRNAs inhibits metastasis to multiple organs, while therapeutic delivery of these LNAs strongly suppresses melanoma metastasis. We thus identify miRNAs with dual cell-intrinsic/cell-extrinsic roles in cancer, reveal convergent cooperativity in a metastatic miRNA network, identify ApoE as an anti-angiogenic and metastasis-suppressive factor, and uncover multiple prognostic miRNAs with synergistic combinatorial therapeutic potential in melanoma.